2018
DOI: 10.1177/1176934318810990
|View full text |Cite
|
Sign up to set email alerts
|

Putative Interaction Proteins of the Ubiquitin Ligase Hrd1 in Magnaporthe oryzae

Abstract: The endoplasmic reticulum (ER) is the entry portal of the conventional secretory pathway where the newly synthesized polypeptides fold, modify, and assemble. The ER responses to the unfolded proteins in its lumen (ER stress) by triggering intracellular signal transduction pathways include the ER-associated degradation (ERAD) pathway and the unfolded protein response (UPR) pathway. In yeast and mammals, the ubiquitin ligase Hrd1 is indispensable for the ERAD pathway, and also Hrd1-mediated ERAD pathway plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…We have identified MoHrd1 (MGG_09205) as a homologue sharing amino acid sequence conservation with Hrd1p in S. cerevisiae (Jiang et al ., 2018). In addition, we performed a BLASTP search of the M. oryzae genome (http://fungidb.org/fungidb/) using the sequence of Der1p from S. cerevisiae as a query and named MoDer1 (MGG_06444).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have identified MoHrd1 (MGG_09205) as a homologue sharing amino acid sequence conservation with Hrd1p in S. cerevisiae (Jiang et al ., 2018). In addition, we performed a BLASTP search of the M. oryzae genome (http://fungidb.org/fungidb/) using the sequence of Der1p from S. cerevisiae as a query and named MoDer1 (MGG_06444).…”
Section: Resultsmentioning
confidence: 99%
“…We previously identified Hrd1 orthologous protein in M. oryzae and found that MoHrd1 could be crucial for the secretory pathway, energy synthesis and metabolism (Jiang et al ., 2018). In the current study, we found that ER‐locating proteins MoHrd1 and MoDer1 play crucial roles in vegetative growth, asexual reproduction and pathogenicity of M. oryzae .…”
Section: Introductionmentioning
confidence: 99%
“…Hrd1 is a key E3 ligase of the endoplasmic reticulum-associated degradation (ERAD) pathway, and MoHrd1 is identified in M. oryzae. IP-MS data to separate putative interacting proteins of MoHrd1 revealed that MoHrd1 is involved in the secretory pathway, energy synthesis and metabolism (Jiang et al 2018). Cell biological and biochemical investigation results showed that both MoHrd1 and MoDer1 have conserved functions in the ERAD system, including ER localization, ERAD substrate degradation and the induction of unfolded protein response (UPR) in their knockout mutants.…”
Section: E3 Ligasementioning
confidence: 99%